The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.1460-9568.2005.04385.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic association of the Ca2+ channel α1A subunit and SNAP‐25 in round or neurite‐emitting chromaffin cells

Abstract: Although the specific interaction between synaptic protein SNAP-25 and the alpha1A subunit of the Cav2.1 channels, which conduct P/Q-type Ca2+ currents, has been confirmed in in vitro-translated proteins and brain membrane studies, the question of how native proteins can establish this association in situ in developing neurons remains to be elucidated. Here we report data regarding this interaction in bovine chromaffin cells natively expressing both proteins. The two carboxyl-terminal splice variants of the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
(83 reference statements)
0
10
0
Order By: Relevance
“…In addition to the evidences yielded by the functional studies aforementioned, molecular techniques have also indicated that P/Q Ca 2+ channels are tightly coupled to the exocytotic machinery in chromaffin cells. Two P/Q channel α 1 subunit isoforms have been identified in bovine chromaffin cells, which share a synprint site and interact with SNAP‐25 in situ (Andrés‐Mateos et al. 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the evidences yielded by the functional studies aforementioned, molecular techniques have also indicated that P/Q Ca 2+ channels are tightly coupled to the exocytotic machinery in chromaffin cells. Two P/Q channel α 1 subunit isoforms have been identified in bovine chromaffin cells, which share a synprint site and interact with SNAP‐25 in situ (Andrés‐Mateos et al. 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that a similar type of interaction between dense core vesicles and Ca 2+ channels may occur for the IRP in chromaffin cells. Previous results that show the feasibility of this hypothesis include the identification of synprint in different splice variants of the P/Q α 1A subunit in bovine chromaffin cells; the co-immunoprecipitation of P/Q channels and the SNARE complex with a monoclonal antibody against SNAP-25; and the co-localization of α 1A and SNAP-25 at the membrane of intact chromaffin cells [20].…”
Section: Introductionmentioning
confidence: 96%
“…In fact, the immunodetection of both variants of the protein in bovine chromaffin cells has been previously reported by our group (Andres-Mateos et al, 2005). In the short variant exon 47 codes only for the stop codon (TAG).…”
Section: Bovine Chromaffin Cells Express Different α 1a Isoforms Origmentioning
confidence: 88%